Gender w polskim dyskursie medialnym na przykładzie publikacji „Gazety Wyborczej” w latach 2010–2014 - Brzoza, Katarzyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
In this article, the main subject of interest is the media image of gender, which is a relatively new phenomenon in the Polish public discourse but arouses strong emotions. The content analysis included materials containing the notion of gender, published in the editorial section of “Gazeta Wyborcza” between 2010–2014. The research showed that the issue of the social and cultural aspects of gender is more and more often present in the public debate, which is strongly polarized in nature. The gathered data allowed for the enumeration of subjects which include the context connected with gender and showed the essence of presenting this subject, in a specific Polish daily newspaper, casting light on the debate in this area.
Gender in polish media discourse based on the example of the newspaper “Gazeta Wyborcza” between 2010-2014
Keywords: gender; content analysis; quantitative analysis; daily; subject matter